CRMP5 Antibodies—Diagnostic Challenges - Totland, Cecilie; Haugen, Mette; Vedeler, Christian (Frontiers in Neurology, 2021)
CRMP5-associated paraneoplastic neurological syndromes (PNS) are rare, and only few studies describe larger cohorts of patients with CRMP5 antibodies. We have included 24 patients with CRMP5 antibodies and compared clinical findings with diagnostic findings from two different line assays (Ravo and Euroimmun), staining of cerebellar sections and results of a newly developed cell-based assay for detection of CRMP5 antibodies, CRMP5-CBA. We found that peripheral neuropathy and cerebellar ataxia together with lung cancer were the most common diagnoses associated with CRMP5 antibodies. CRMP5-CBA was easy to perform, identified all relevant cases for CRMP5-associated PNS and is therefore a valuable add-on for verification of CRMP5 positivity in diagnosis of PNS.